In planta transformation of three Bangladeshi tomato varieties with a vacuolar antiporter - Rahman, Md. Mubassir (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfillment of the requirement for the degree of B.Sc in Biotechnology, 2017.